Appointment with a stranger - Thesman, Jean. (Boston : Houghton Mifflin, 1989)
Deeply self-conscious about her severe asthma attacks, high school student Keller Parrish finds solace in the company of an attractive but mysterious boy at a remote pond, unaware that he is an insubstantial echo of a forty-year-old tragedy.
Booklist.
6.8
6.8
5-8.
5-8
Keywords: Asthma -- Fiction; Ghosts -- Fiction; Physically handicapped -- Fiction; Asthma -- Fiction; Ghost stories; Physically handicapped -- Fiction